ANALISIS KESULITAN SISWA KELAS V SDS PESANTREN YPMA DALAM MENGUASAI TEKNIK DASAR PERMAINAN BOLA KASTI PADA MATA PELAJARAN PJOK - Putri Balqis Ar Raudhah; Winara; Nurhairani; Khairul Usman; Natalia Silalahi (STKIP Subang, 2026)
Physical Education, Sports, and Health (PJOK) plays a crucial role in shaping a healthy and skilled generation. At SDS Pesantren YPMA, many fifth-grade students experience difficulties in mastering the basic techniques of baseball, indicating the presence of inhibiting factors that require further analysis. This study aims to analyze the factors that contribute to students' difficulties in mastering the basic techniques of baseball in the PJOK subject in fifth-grade students at SDS Pesantren YPMA. The method used in this study is a descriptive qualitative approach, with data collection through observation, interviews, and questionnaires. The results show that internal factors such as lack of self-confidence (70%), fear of the ball (60%), and external factors such as limited facilities (75%) and limited practice time (65%) significantly influence mastery of basic techniques. Overall, internal factors contribute 60% to the difficulties experienced by students, while external factors contribute 65%. In addition, low student motivation (50%) and lack of variation in teaching methods (55%) also exacerbate the situation. Based on the research results, it can be concluded that the difficulties faced by fifth-grade students of SDS Pesantren YPMA in mastering the basic techniques of baseball are influenced by various internal and external factors. Therefore, to improve mastery of the basic techniques of baseball, it is recommended to provide a more innovative and interesting learning approach, increase student motivation, and provide more adequate facilities so that students can practice optimally and achieve better results in PJOK learning.